Hypogammaglobulinemia in Children After Hematopoietic Stem Cell Transplantation and Rituximab Treatment: Relevance of B Cell Subsets. Issue 1 (17th January 2023) - Marzollo, Antonio; Serena, Tiziana; Mainardi, Chiara; Calore, Elisabetta; Pillon, Marta; Carraro, Elisa; Tosato, Francesca; Biffi, Alessandra; Tumino, Manuela
Abstract : Rituximab (RTX) is widely employed to treat Epstein-Barr virus reactivation in children undergoing Hematopoietic Cell Transplantation (HCT). The resulting loss of B cells may cause persistent hypogammaglobulinemia. This retrospective cross-sectional study aims to identify flow cytometry biomarkers associated with persistent hypogammaglobulinemia in patients receiving RTX after HCT. We analyzed 5 patients (cases group) requiring immunoglobulin substitution due to low level of IgG (IgG <5 g/L) detected after RTX treatment and 5 patients (controls group) not requiring long-term immunoglobulin (Ig) substitution. We investigated the B cell reconstitution, and in patients group we observed a significantly lower count in B total, IgD+CD27+ marginal B cells and IgD-CD27+ switched-memory B cells, after a median of 5 years from HCT, compared with the control group. Despite the importance limits of our study and the heterogeneity of our data (age of included patients, time of evaluation, interval between RTX dose and assessment) we conclude that RTX given early after HCT might cause a deranged B cell maturation, contributing to the delation in B cell recovery following HCT, and switched memory and marginal zone B cell counts could be a promising biomarker to identify patients requiring long-term Ig substitution.